Analisis struktur ekonomi daerah berbasis pertambangan: indikasi enclave economy di Kabupaten Sumbawa Barat - Faizatul Amala; Aheruddin Aheruddin (Nur Science Institute, 2026)
West Sumbawa Regency has an economic structure that is highly dependent on the mining sector, with an average contribution of 65–82% to the GRDP during the 2010–2023 period. This study aims to identify base sectors, analyze regional competitiveness, examine indications of an enclave economy, and determine potential sectors for post-mining economic diversification. The method used is a quantitative descriptive-analytical approach by utilizing secondary data of sectoral GRDP for 2010–2023. The analysis was conducted using Location Quotient (LQ), Shift-Share, Esteban-Marquillas, Overlay Analysis, and Klassen Typology. The results show that the mining sector is the main base sector with an LQ value of 4.67. Shift-Share analysis indicates that the construction, agriculture, and transportation sectors have relatively high competitive advantages. Meanwhile, Esteban-Marquillas' analysis shows that the mining sector is in a decline phase characterized by negative Competitive Effect and Allocation Effect values. Klassen Typology shows that there are no sectors in Quadrant I, thus reflecting weak economic diversification. These findings indicate strong enclave economy characteristics with still low sectoral linkages to regional economic transformation.